IMPROVING STUDENTS’ READING COMPREHENSION THROUGH COOPERATIVE SCRIPT TECHNIQUE OF FIRST GRADE AT SMK NEGERI 1 TOLITOLI - Mohammad Rafi'i (Universitas Madako Tolitoli, 2019)
The objective of this research is to find out whether the application of cooperative script technique improve the students’ reading comprehension or not. It is a pre-experimental research. It conducted at first grade of SMK Negeri 1 Tolitoli that was X PK 1 in academic year 2016/2017. The writer gave a pre-test to measure the students’ previous ability in reading comprehension. Then, a post-test to find out the students’ reading comprehension after given treatment which is the application of cooperative script technique. The writer used SPSS 16.0 program to analyze the data. The result of data analysis showed that cooperative script technique give a significant effect to the students in comprehending a recount text. The mean score of the post-test (82,67) was higher than the mean score of pre-test (69,87). Then, the testing hypothesis showed that the value of Tcount was greater than Ttable (13.797 > 2.054). In conclusion, the application of cooperative script technique is effective to improve students’ reading comprehension in recount text. Key words: Improving, Reading Comprehension, and Cooperative Script.